ANALYSIS OF SERUM IRON AND HEAMOGLOBIN LEVEL IN PATIENTS WITH ORAL SUBMUCOUS FIBROSIS - Urooj, Arsala; Anwar Ali,; Akbar Agha,; Syed, Syed Israr Ahmed; Marium Zaheer, (Journal of Ayub Medical College Abbottabad, 2022)
Background: OSMF is chronic underlying disease. The disease is well recognized and had an importance due to high malignant transformation rate. Multiple etiological factors are found responsible in the pathogenesis of the disease course. The effect of areca-nut is mainly causing trismus of the oral cavity. This may compromise the food intake of the patients who are facing this precancerous disease. Method: Total one hundred and 28 patients were selected and equally distributed into two groups. It is an observational, cross- sectional study. Sixty four patient with OSMF were selected on the basis of fibrous band formation and mouth opening. The etiological factors such as chewing habit had been denoted in forms. The heamoglobin and iron levels were analyzed from laboratory using automated machines used for blood analysis. Results: The OSMF group showed insignificant variation when the two groups were compared. Whereas the sub-groups of OSMF are showing moderately significant correlation for the serum iron and heamoglobin levels. The outcome of the present study emphases on the assessment of heamoglobin and serum iron for OSMF patients. The patients must be prescribed with the micronutrients therapy so that any deficiency which may contribute in the disease course can be intercepted at the beginning. Further the patients must be educated in term of quitting the chewing habit so that his/ her life not get compromised due to OSMF.